PERUBAHAN KONSEPTUAL DALAM PEMBELAJARAN SAINS ANAK USIA SEKOLAH DASAR - Lily Barlia (LPMPP Universitas Negeri Yogyakarta, 2009)
The conceptual change model (CCM) provides teachers with an opportunity to think about the best means to make students learn scientific concepts for understanding. The learning process should be based on the objective to facilitate the formation of students metacognitive ability so that a learning process for a conceptual change can take place. A conceptual change can take place because basically each individual confronts and evaluates the newly acquired concepts in accordance with intelligibility, plausibility, and fruitfulness. This article discusses CCM and the possibility of students conceptual change to occur as a result of science learning. Theoretically, CCM is supported by two factors, namely 1) the status of a concept, explained in terms of intelligibility, plausibility, and fruitfulness, and 2) the components of conceptual ecology, i.e. how an individual determines the truth of a concept. The two factors have a great influence on what students learn and how they evaluate the truth of an available concept. Besides, a conceptual change, in some cases, occurs when students commitments as learning outcomes are in agreement with conceptual ecology that they have possessed or they can understand scientifically. Regardless of the types of concepts that students hold, teachers have an obligation to create a learning process that facilitates the formation of students metacognitive ability because this is important for a conceptual change. Keywords: conceptual change, Conceptual Change Model, conceptual under-standing, science learning